Pencegahan Stunting Melalui Penguatan Ketahanan Pangan Bagi Masyarakat Desa Kumpi Kecamatan Lembo Kabupaten Morowali Utara - Delfince Tjenemundan; Feliks Arfid Guampe; Olvit Olniwati Kayupa; Cirtye Labesani; Melky Alfian (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting is the most serious nutritional problem in Indonesia, caused by inadequate nutritional intake. This condition is characterized by impaired growth, where children's height is shorter compared to the average height of children their age. Stunting can be prevented if interventions are carried out before the child reaches the age of two to five years. In Kumpi Village, one child was found to be at risk of Stunting. To prevent Stunting, knowledge transfer through training and community mentoring is needed, one of which is by strengthening food security. This activity uses an active participation method and involves various activities such as "nutrition Friday" at Tunas Harapan Kindergarten and PAUD, giving parcels to children at risk of Stunting, "clean Saturday" activities, the "smart kindergarten" program, utilizing home yards for cultivation, distributing catfish seeds, planting organic vegetables, and making liquid organic fertilizer. The results of this activity indicate that the community of Kumpi Village understands that Stunting can be addressed through improved food security and environmental support. This activity has significant implications for Stunting eradication strategies through community empowerment and enhanced food security.